2019
DOI: 10.1109/access.2019.2928979
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Review of Artificial Intelligence Applied in the Fashion and Apparel Industry

Abstract: The enormous impact of artificial intelligence has been realized in transforming the fashion and apparel industry in the past decades. However, the research in this domain is scattered and mainly focuses on one of the stages of the supply chain. Due to this, it is difficult to comprehend the work conducted in the distinct domain of the fashion and apparel industry. Therefore, this paper aims to study the impact and the significance of artificial intelligence in the fashion and apparel industry in the last deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 156 publications
0
51
0
1
Order By: Relevance
“…Real-time in-store video data is processed to make recommendations for new garment purchases [50]. The comprehensive literature review identified a research gap in the application of ML and AI in the fashion and apparel industry [51]. Combining state-of-the-art computer vision techniques with marketing models of consumer preferences, the system automatically identifies shoppers' preferences based on their reactions and it uses that information to make meaningful personalised recommendations [50].…”
Section: Product and Purchasing Decision-makingmentioning
confidence: 99%
“…Real-time in-store video data is processed to make recommendations for new garment purchases [50]. The comprehensive literature review identified a research gap in the application of ML and AI in the fashion and apparel industry [51]. Combining state-of-the-art computer vision techniques with marketing models of consumer preferences, the system automatically identifies shoppers' preferences based on their reactions and it uses that information to make meaningful personalised recommendations [50].…”
Section: Product and Purchasing Decision-makingmentioning
confidence: 99%
“…Its review is more theoretical than practical. [29] reviewed AI but only applied in the fashion and apparel industry and to find gaps in the application of AI techniques. In contrast, we considered other groups like transportation, communication, or agriculture, and to find the practical use of AI based on specific methods or techniques.…”
Section: Discussionmentioning
confidence: 99%
“…The field is rather being constantly redefined when some topics are classified as non-AI, and new topics emerge". We found papers that have tracked the progress of AI research through the number of published papers [22], or that have discussed "problems, challenges and opportunities in AI" [60], or that have made a detailed review of AI applied in the fashion and apparel industry [29], but they do not have an explanation of what is AI or what are the practical implications in a broader scope or other industries. For that reason, we did a systemic review of most cited papers in the topic "Intelligent Systems in the Internet of Things (IoT)" to answer these questions and to fill this gap between the theory and practice of AI in IoT.…”
Section: Introductionmentioning
confidence: 99%
“…The number of AI led B2C articles published over last 2 decades was miniscule, however they have advocated the requirement of AI to be instrumental in capturing consumer needs and preferences accurately and conveniently (Giri, Jain, Zeng & Bruniaux, 2019). Artificial Intelligence was used to personalize the advertising efforts, which led to a better understanding of the product with the consumer (Even Deng, Tan, Wang & Pan, 2019).…”
Section: Research Objectives and Methodologymentioning
confidence: 99%